2020
DOI: 10.1212/wnl.0000000000010733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of escitalopram on Aβ levels and plaque load in an Alzheimer mouse model

Abstract: Rationale:Several neurotransmitter receptors activate signaling pathways that alter processing of the amyloid precursor protein (APP) into amyloid-β (Aβ). Serotonin signaling through a subset of serotonin receptors suppresses Aβ generation. We proposed that escitalopram, the most specific selective serotonin reuptake inhibitor (SSRI) that inhibits the serotonin transporter , SERT, would suppress Aβ levels in mice.Objectives:We hypothesized that acute treatment with ESC would reduce Aβ generation which would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 37 publications
1
33
1
Order By: Relevance
“…SSRIs, which increase serotonin levels in the brain, show promise for reduction of Aβ accumulation in both the brain and CSF. Studies in APP/PS1 transgenic mice showed that the SSRI citalopram caused a 50% reduction in brain amyloid plaque load, and escitalopram, citalopram's S-isomer, reduced interstitial fluid Aβ by 25% 81,82 . A controlled clinical trial of cognitively normal adults showed that escitalopram could decrease CSF Aβ42 levels in humans, with a difference of 11.1% between the control and treatment groups 83 .…”
Section: Discussionmentioning
confidence: 99%
“…SSRIs, which increase serotonin levels in the brain, show promise for reduction of Aβ accumulation in both the brain and CSF. Studies in APP/PS1 transgenic mice showed that the SSRI citalopram caused a 50% reduction in brain amyloid plaque load, and escitalopram, citalopram's S-isomer, reduced interstitial fluid Aβ by 25% 81,82 . A controlled clinical trial of cognitively normal adults showed that escitalopram could decrease CSF Aβ42 levels in humans, with a difference of 11.1% between the control and treatment groups 83 .…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports that antidepressants from the SSRI group exhibit neuroprotective effects with a diverse mechanism of action. Preclinical and clinical studies indicate beneficial effects on cognitive function [ 14 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Furthermore, literature data indicate that SSRIs “ increase neurotrophic factors including brain-derived neurotrophic factor, promote neurogenesis in the hippocampus, and reduce levels of toxic Aβ ” [ 124 ].…”
Section: Selective Serotonin Reuptake Inhibitors (Ssri)mentioning
confidence: 99%
“…Another drug being considered as a candidate for the treatment of AD is escitalopram, the most specific selective serotonin reuptake inhibitor [ 119 ].…”
Section: Selective Serotonin Reuptake Inhibitors (Ssri)mentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin infusion into the brain decreases Aβ by reducing its production. Cirrito et al found that citalopram and escitalopram administered to mice acutely decreased Aβ levels by 25 % within eight hours while chronic administration decreased plaque deposition even further by increasing α-secretase activity [56][57][58][59]. Chronic reduction in Aβ levels lowers the risk of accumulating toxic conformations that produce amyloid plaques.…”
Section: Prevention Of Alzheimer's Dementiamentioning
confidence: 99%